The Bekasi City Fire Department’s Disaster Communication Socialization at SMK Vinama 2 Bekasi - Aditya Maulana Yusuf; Wa Ode Sitti Nurhaliza; Dinar Soelistyowati; Annisa Eka Syafrina (Momentum Matrix: International Journal of Communication, Tourism, and Social Economic Trends, 2024)
Abstract: This study explores the communication patterns used by the Fire and Rescue Department of Bekasi City in disseminating fire disaster mitigation education at SMK Vinama 2 Bekasi. The research investigates how disaster communication is implemented through socialization programs aimed at increasing students’ awareness and preparedness toward fire hazards. Using a qualitative descriptive approach, data were collected through interviews, observation, and documentation with key informants, including officials from the Prevention Division, school representatives, and student participants. The findings reveal that the department adopts a multi-layered communication model integrating one-way, two-way, and multi-way approaches to effectively convey safety messages. The process involves formal coordination, practical demonstrations, and participatory simulations, contributing to improved literacy and proactive attitudes among students. This study highlights the essential role of structured communication patterns in enhancing disaster preparedness and proposes recommendations for strengthening participatory engagement in future educational programs.